A study of relationship between training and development and self-esteem among public servant in Kota Kinabalu City Hall / Albayinah Dutch and Hairin Nihma Fardo - Dutch, Albayinah; Fardo, Hairin Nihma (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2012)
Every organization prepare for training and development to make sure the employee in the organization are increase their skill and performance. In addition it is also to ensure that the employee will increase the self-esteem among their self. The purpose of this research is to study the relationship between training and development and self-esteem . It is to see whether there is a significant of the relationship. On this research, questionnaires are distributed to the staff at Kata Kinabalu City Hall. The training and development and self-esteem are important and relate with each other. Without training and development the employee self-esteem towards the jobs will not be achieve by the organization in producing an efficiency and effectiveness employees. Random samples of 70 employees from four departments in KKCH were distributed by questionnaire. Through output gathered, there is significant relationship between training and development and self-esteem. The employees in KKCH give positive response and mostly agreed that training and development and self-esteem are related with each other.